DECENT WORK ON FOOD INDUSTRY BY USING ADEQUATE INCOME AND SOCIAL SECURITY MEASUREMENT - Hartato Hartato (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2019)
Abstract The role of food industry as a labor intensive subsector must be able to guarantee labors to provide basic rights such as adequate income social security guarantees for a prosperous and decent life. Based on results of National Labor Force Survey (Sakernas) August 2018 showed that this subsector was dominated by labors with inadequate working conditions at 75.13 percent which means their wages received during the month were less than 2/3 the median value of the national average income, Rp1,500,000,- and didn’t get social security guarantees almost three times compared to other industrial subsectors. This paper aims to study the effect tendency of job, company, and individual characteristics toward decent work by using binary logistic regression with data of Sakernas August 2018. The results of this paper with 3,860 labors show that education level is variable with the highest effect toward decent work at food industry. In addition, labors on blue collar occupation, no employment agreement, low education, non profit business with a paid per unit wage system will risk being classified as improper work. The conclusion is generally labors on food industry still called as inadequate worker with low education so that they work on blue collar occupationand it imply to their income social security guarantees.Therefore,investment through education is needed to improve the quality of human capital as workersand finally it can compensate labors to obtain better job feasibility standard.